Diurnal regulation of sphingolipids in blood - Brunkhorst, Robert; Pfeilschifter, Waltraud; Rajkovic, Natasa; Pfeffer, Martina; Fischer, Claudia; Korf, Horst-Werner; Christoffersen, Christina; Trautmann, Sandra; Thomas, Dominique; Pfeilschifter, Josef; Koch, Alexander (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2019)
Key homeostatic functions are regulated in a diurnal manner and a miss-alignment of such rhythms is believed to contribute to the pathophysiology of several diseases. Signaling sphingolipids (SLs) in plasma such as sphingosine 1-phosphate control lymphocytic trafficking, vascular reactivity and platelet activity, physiological functions all of which display a diurnal rhythm themselves. However, the rhythmicity of SL metabolism in plasma and its potential causes have not been sufficiently investigated so far. Therefore, we analyzed blood of mice and healthy adult human subjects by targeted tandem mass-spectrometry at different time points. In order to investigate the influence of the synchronizing hormone melatonin, we compared melatonin proficient C3H/HeN wildtype mice (C3H) with melatonin receptor-1/2 double knockout mice (MT1/2−/−) and melatonin deficient C57BL/6J mice. We found a strong upregulation of plasma S1P with the beginning of the light period in C3H but not in MT1/2−/− or C57BL/6J mice. Accordingly, our study revealed an upregulation of sphingosine 1-phosphate (S1P d18:1) and sphinganine 1-phosphate (S1P d18:0) with the beginning of the light period in humans. Furthermore, plasma S1P d18:1 and S1P d18:0 were inversely correlated with the respective concentrations in platelets, pointing to a possible involvement of platelet SL metabolism. In humans, the diurnal rhythm of SLs was not associated with changes of SL-binding proteins or counts of cellular SL sources. Overall, this study indicates a physiological rhythmicity of plasma and platelet SL metabolism, likely mediated by melatonin, with potentially important implications for physiological diurnal rhythms and the regulation of SL metabolism and its functions. •Sphingolipids are diurnally regulated in human and mouse plasma.•The diurnal regulation of sphingosine 1-phosphate and sphinganine 1-phosphate is dependent on intact melatonin signalling.•Sphingosine 1-phosphate in human plasma is associated by alterations of sphingosine 1-phosphate concentrations in platelets.•Sphingolipids in human plasma is independent of a regulation of sphingolipid chaperons and sphingolipid producing cells.